CONCURRENT CHEMOTHERAPY-RELATED SYSTEMIC TOXICITIES DURING BREAST CANCER TREATMENT: AN OBSERVATIONAL AND PROSPECTIVE REPORT - Matias Lordelo Marinho, Pabliane (2022)
Objective: to quantitatively evaluate a cluster of chemotherapy-related systemic toxicities in women with breast cancer throughout treatment. Method: an observational, prospective and quantitative study was carried out, involving 140 women with breast cancer exposed to chemotherapy as a treatment modality. The occurrence of 14 systemic toxicities (based on the Common Terminology Criteria for Adverse Events, version 4.03) was evaluated in the medical charts in two segments: in the intermediate cycle and at the end of chemotherapy. The frequencies were compared between the two study segments, associating each toxicity separately and grouping the amount of simultaneous toxicities of each patient, considering the significance level (p) of 5%. Results: it was observed that most systemic toxicities were associated between the segments of the study, as well as most manifested more frequently at the end of chemotherapy. The most frequent toxicities (considering both segments) were vomiting (90.7%), headache (88.6%) and asthenia (87.9%). The most uncommon were leukopenia (7.1%), neutropenia (13.6%) and paresthesia (32.1%). When comparing the amount of concurrent systemic toxicities between the segments, a significant increase was observed at the end of chemotherapy in relation to the intermediate cycle (p <.001). Conclusion: women with breast cancer experienced a greater amount of concurrent systemic toxicities at the end of chemotherapy, as well as a high frequency of systemic toxicities throughout treatment was observed.